A broadband composite complementary double‐split rectangular metamaterial absorber for planar microwave circuits. Issue 11 (8th July 2019) - Bai, Ningfeng; Shen, Jingxuan; Shen, Changsheng; Sun, Xiaohan; Pan, Pan; Jun, Cai; Feng, Jinjun
Abstract: In this article, we present a broadband metamaterial absorber (MA) designed for planar microwave circuits, which focuses on the absorption of an electromagnetic wave (EMW) that flows parallel to the direction of the transmission. This MA consists of complementary double‐split rectangles (CDSRs) with a dielectric layer on top of a metallic ground plane, which can be added to a planar microwave circuit as a bottom layer to absorb the EMWs. With further optimization, a composite CDSR‐MA is proposed that operates between 6.5 GHz and 11.2 GHz and covers X‐band communication frequencies. Modeling and simulation is performed using the CST studio software. The absorption bandwidth of this CCDSR‐MA is 6.5‐11.2 GHz, with absorption above 0.75 and the maximum absorption reaches 0.96 at 10.2 GHz. A sample on a five‐layered circuit board using standard print circuit board technology is fabricated to test this CCDSR‐MA, with an outer dimension of 13.4 mm × 137 mm. The simulation and experimental results agree well with each other.